Isopimarane-type diterpenoids from Croton laevigatus. Issue 20 (17th October 2020) - Li, Man-Yu; Han, Zheng-Zhi; Liu, Li-Fang; Wu, Xiao-Zhen; Huang, Wen-Jun; Wang, Kai; Yang, Fan; Yuan, Cheng-Shan
Abstract: A new isopimarane-type diterpenoid, crolaevinoid A, along with four known analogues was isolated from the twigs and leaves of Croton laevigatus . The structures of the isolated compounds were established on the basis of NMR and MS spectroscopic analyses. The isolated compounds were examined the antibacterial activities. Unfortunately, the compounds showed no antibacterial activity against Micrococcus luteus, Methicillin-resistant Staphylococcus aureus, Aeromonas hydrophila, Klebsiella pneumoniae ssp pneumoniae, Acinetobacter Baumanii, and Escherichia coli. Abstract :